Mapping zero-dose children in Kenya – A spatial analysis and examination of the socio-demographic and media exposure determinants - Judy Gichuki; Ben Ngoye; Donnie Mategula (PLoS ONE, 2025)
Despite vaccines’ proven effectiveness in preventing childhood diseases, there remains a significant population of unvaccinated children, often referred to as zero-dose children. This study examines the factors contributing to the prevalence of zero-dose children in Kenya using data from the 2022 Kenya Demographic and Health Survey (KDHS). We included all children aged 1–35 months who had not received any vaccination during the survey. In the analysis, we utilized logistic regression to explore the determinants of zero-dose status, including the mothers’ media exposure. We also employed model-based geostatistical methods to determine the fine-scale spatial distribution of zero-dose children in Kenya. Our findings reveal the disparities in the prevalence of zero-dose children, with specific regions such as Tana River, Marsabit, Turkana, and Isiolo in the north exhibiting distinct hotspots. Children aged 12–23 (aOR = 0.41; 95% CI: 0.24, 0.68) and 24–35 (aOR = 0.33; 95% CI: 0.18, 0.57) had lower odds of being zero dose than those 1–11 months of age. Compared to women who had no antenatal visits, women who attended four and above visits had 88% lower odds of having a zero-dose child (aOR=0.12;95% CI 0.05–0.27; p<0.001), while those who attended three visits had 91% lower odds of having a zero-dose child (aOR=0.09; 95% CI 0.04–0.19; p<0.001). Additional factors associated with zero-dose status included the education level, wealth index, religion, place of delivery, travel time to the nearest facility, listening to the radio, mother’s mobile phone ownership, and mother’s phone use for financial transactions. The results emphasize the unique contextual factors associated with zero-dose status, underscoring the need for tailoring public health interventions to specific socio-cultural and economic environments. While findings should be interpreted with care due to the complexity of relationships between variables, they highlight the necessity for targeted immunization initiatives that cater to the distinct needs of various regions and demographic groups. We recommend implementing enhanced education and awareness campaigns, addressing socio-economic barriers, and considering caregiver socio-behavioral factors as crucial to improving immunization coverage in Kenya.